2018
DOI: 10.1111/padm.12403
|View full text |Cite
|
Sign up to set email alerts
|

Public or nonprofit? Career preferences and dimensions of public service motivation

Abstract: While the foundational claim that PSM attracts individuals to the public sector is well established in the research literature, much uncertainty still exists about its influence on the choice between the public versus the nonprofit sector, which also frequently exhibits a strong public service mission. Little is known also about how discrete dimensions of PSM differ in their effects on such job preferences. This article addresses these shortcomings by drawing on a study that combines the measurement of separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 41 publications
(85 reference statements)
1
23
0
Order By: Relevance
“…It is critical to examine theories in many empirical contexts as the public administration and management research community becomes increasingly internationalized. The research also contributes to the wide variety of work considering institutional differences among employees and organizations across the public, private, and nonprofit sectors (e.g., Boyne et al 1999;Rainey and Bozeman 2000;Johnston 2017;Ballart and Rico 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is critical to examine theories in many empirical contexts as the public administration and management research community becomes increasingly internationalized. The research also contributes to the wide variety of work considering institutional differences among employees and organizations across the public, private, and nonprofit sectors (e.g., Boyne et al 1999;Rainey and Bozeman 2000;Johnston 2017;Ballart and Rico 2018).…”
Section: Discussionmentioning
confidence: 99%
“…After excluding unmatched surveys and those with missing data, 165 valid observations were collected: 99 are third-year students of a Bachelor degree program in Business and Economics a in the Netherlands, and 66 are first-year Master students in Business and Economics in the Dutch-speaking part of Belgium. Undergraduate students are regularly used in Public Administration, being well suited to test the relation between core personality characteristics and PSM (see, e.g., Perry, 1996 ; Christensen and Wright, 2011 ; van Witteloostuijn et al, 2017 ; Ballart and Rico, 2018 ). Even though the parental socialization process in general and the profession of someone’s parents in particular impact a person’s level of PSM ( Anderfuhren-Biget, 2012 ), students have limited work experience, which makes their PSM less affected by context due to work socialization and other sources of job-related variance ( van Witteloostuijn et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, much of our knowledge is based on cross-sectional studies or studies using very controlled treatments and/or short delays between inducing a treatment and measuring the response (e.g., Grant 2008;Bellé 2014). A problem with cross-sectional studies is endogeneity, that is, the possibility that people select into administrative environments that match their preferences (Anderfuhren-Biget et al 2014;Ballart and Rico 2018), and this process of selection may explain observed correlations between some environmental characteristics and individual motivation. In pointing to the endogeneity problem in studies of motivation, Vandenabeele et al (2014, p. 783) emphasize that this is not merely a methodological challenge.…”
mentioning
confidence: 99%